The productions of childhood in the poetry of Herberto Helder: territories without height, disobedience of language - Panzini, Renata [UNESP] (My University, 2022)
This article focuses on exploring the multiple appearances of the idea of childhood in the poetry of the Portuguese writer Herberto Helder (1930-2015), from two theoretical basis: 1. From the American poet and literary critic Ezra Pound, from whom we will propose approximations between his conception of logopeia (“the dance of the intellect”), and the childhood images in Helder's poetics; and 2. From the french philosopher Gilles Deleuze, from which we will borrow the concept of becoming, in order to connect it to the childhood imagination engaged in Helder's poems. The desire that move these approximations is to scrutinize the childhood ideals in Herberto Helder's poems from two registers: that of form (as materiality), and for this reason we will try to bring to light the rational dimension of the author's poetry; and that of thought, which we will investigate the dimension contained in such productions.
As produções de infância na poesia de Herberto Helder: territórios sem altura, desobediência da linguagem
Keywords: Childhood; Ezra Pound; Gilles Deleuze; Herberto Helder; Portuguese poetry